Applications of Matrix Metalloproteinase-9-Related Nanomedicines in Tumors and Vascular Diseases - Xuying Li; Zhuping Xu (Pharmaceutics)
Matrix metalloproteinase-9 (MMP-9) is implicated in tumor progression and vascular diseases, contributing to angiogenesis, metastasis, and extracellular matrix degradation. This review comprehensively examines the relationship between MMP-9 and these pathologies, exploring the underlying molecular mechanisms and signaling pathways involved. Specifically, we discuss the contribution of MMP-9 to tumor epithelial–mesenchymal transition, angiogenesis, and metastasis, as well as its involvement in a spectrum of vascular diseases, including macrovascular, cerebrovascular, and ocular vascular diseases. This review focuses on recent advances in MMP-9-targeted nanomedicine strategies, highlighting the design and application of responsive nanoparticles for enhanced drug delivery. These nanotherapeutic strategies leverage MMP-9 overexpression to achieve targeted drug release, improved tumor penetration, and reduced systemic toxicity. We explore various nanoparticle platforms, such as liposomes and polymer nanoparticles, and discuss their mechanisms of action, including degradation, drug release, and targeting specificity. Finally, we address the challenges posed by the heterogeneity of MMP-9 expression and their implications for personalized therapies. Ultimately, this review underscores the diagnostic and therapeutic potential of MMP-9-targeted nanomedicines against tumors and vascular diseases.